Effects of Monoglycerides of Varying Fatty Acid Chain Length and Mixtures Thereof on Sponge‐and‐Dough Breadmaking Quality. Issue 5 (18th May 2015) - Hattori, Kazuki; Dupuis, Brigitte; Fu, Bin Xiao; Edwards, Nancy M.
Abstract : Monoglycerides are widely used in the baking industry because of their antistaling effects, mainly suppressing crumb firming. Commercial monoglycerides are normally prepared from hydrogenated fats, with stearate being the most common fatty acid. In a previous study, monoglycerides such as monopalmitate (C16) and monostearate (C18) had positive effects on Canadian short process bread but no improvements on sponge‐and‐dough process (SDP) bread. The objective of this study was to investigate the effects of saturated monoglycerides of varying fatty acid chain length (C14–C22) on SDP breadmaking quality by using volume judgment, crumb image analysis, and texture measurements. Higher levels (1.00–1.50%) of all monoglycerides (C14, C16, and C18) significantly ( P < 0.05) increased loaf volume and cell diameter. The larger cell diameter with increasing levels of these monoglycerides may have resulted from softer, more extensible dough handling properties and greater gas cell stability during baking. Addition of C16 and C18 caused the largest increase in crumb softness with increasing monoglyceride levels but showed relatively low resilience, which might be related to larger loaf volume (i.e., lower density of bread). However, addition of blended monoglycerides C14+C16 increased crumb softness and loaf volume while partially retaining resilience. Each monoglyceride had a different function in breadmaking quality and somewhat positive effects on SDP.